An experimental investigation on the influence of rotational speed on microstructure and mechanical properties of friction stir welded dissimilar Al-Cu joints. (25th September 2020) - Medhi, Tanmoy; Roy, Barnik Saha; Saha, Subhash Chandra
The present study focuses on understanding the effect of variation of rotational speed on microstructure and mechanical properties of friction stir welded joints. AA 6061-T6 and pure copper 3 mm plates were welded at 800 rpm, 1, 000 rpm, 1, 500 rpm and 1, 800 rpm using a constant traverse speed of 60 mm/min. Alterations on forces and torque, weld morphology, macrostructure, microstructure and formation of intermetallics were observed. A detailed electron dispersive spectrum (EDS) and X-ray diffraction (XRD) analysis showed the formation of Al2 O3 and CuO along with Al2 Cu and Al4 Cu9 at higher rotational speed in the nugget zone (NZ). These intermetallics and oxides resulted in an inhomogeneous distribution of hardness at 1, 800 rpm but due to presence of micro-defects the values were comparatively lower. Joint efficiency of 77% is achieved at 1, 000 rpm which may be due to strengthening effect by the intermetallics. The joint strength deteriorated at 1, 500 rpm and 1, 800 rpm due to the presence of oxides making the joints brittle.